Mechanical and durability performance of talc ore additive calcium aluminate cement-based mortars reinforced with hybrid fibers - Kaman, Alperen; Yilmaz, Arin; Aygormez, Yurdakul (ELSEVIER SCIENCE SA, 2026)
Calcium Aluminate Cement (CAC) mixtures offer an alternative product. However, the binders used as substitutes for CAC are limited. In this study, ground talc ore was substituted for CAC at specific ratios (0%, 5%, 10%, 15%, and 20%). In the series where talc was used at 0%, 5%, and 10%, yielding the best results, microfiber was substituted at 0%, 0.3%, 0.6%, and 0.9%. Additionally, compressive and flexural strength tests were conducted at 7, 28, and 90 days. To determine durability performance, a high-temperature test (250, 500, and 750 degrees C), a freeze-thaw test (100 cycles), 10% magnesium sulfate (MgSO4) and 10% sodium sulfate (Na2SO4) solutions for 2 and 3 months were conducted. After the tests, compressive and flexural strengths and weight values were compared. XRD, TGA-DTA, and SEM analyzes were also conducted. The results indicated that talc ore substitution had a negative effect on the results due to its reduced cement content, while increasing SiO2 and MgO contents also had positive effects on the strength results, particularly after durability effects. Microfiber was found to increase ductility and resistance to first cracks. In general, the evaluation of talc ore substitution is beneficial from the point of view of evaluating sustainable and cost-effective building materials.
Keywords: Calcium aluminate cement; Talc ore; Microfiber; Durability tests; HIGH-TEMPERATURE RESISTANCE; STRENGTH; POLYPROPYLENE; BEHAVIOR; ASH; Materials Science